2021
DOI: 10.1097/md.0000000000025653
|View full text |Cite
|
Sign up to set email alerts
|

Efficacy and safety of Xuanfei Baidu granules for treating COVID-19

Abstract: Background: Corona Virus Disease 2019 (COVID-19) is currently prevalent in most countries around the world. It has become a common threat to global human health because there is no specific cure and no targeted treatment for this disease at this stage. Xuanfei Baidu granule (XFBD) included the traditional Chinese medicine prescription in COVID-19 diagnosis and treatment Plan (trial eighth Edition) released in August 2020, which has played a great role in the diagnosis and treatment of COVID-19 in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 10 publications
(15 reference statements)
0
7
0
Order By: Relevance
“…Patients' questions often relate to Chinese herbal medicine (CHM) as a popular representative of alternative medicine. Currently, protocols of systematic reviews and meta-analyses for 7 preparations have been announced: Shufeng Jiedu ( Wang et al, 2020a ), Xuanfei Baidu ( Zhao et al, 2021 ), Maxingshigan Decoction ( Shao et al, 2020 ), Reyanning mixture ( Li et al, 2021 ), Xiaoqinglong decoction ( Ren et al, 2020 ), Lianhua Qingwen ( Liu et al, 2020a ), and Xiyanping ( Zhou et al, 2020 ). As the authors suggest, these drugs have been used to treat COVID-19 in China, so scientific evidence is needed to evaluate their effectiveness.…”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 99%
“…Patients' questions often relate to Chinese herbal medicine (CHM) as a popular representative of alternative medicine. Currently, protocols of systematic reviews and meta-analyses for 7 preparations have been announced: Shufeng Jiedu ( Wang et al, 2020a ), Xuanfei Baidu ( Zhao et al, 2021 ), Maxingshigan Decoction ( Shao et al, 2020 ), Reyanning mixture ( Li et al, 2021 ), Xiaoqinglong decoction ( Ren et al, 2020 ), Lianhua Qingwen ( Liu et al, 2020a ), and Xiyanping ( Zhou et al, 2020 ). As the authors suggest, these drugs have been used to treat COVID-19 in China, so scientific evidence is needed to evaluate their effectiveness.…”
Section: Other Agents Tested For Potential Efficacy In Treating Covid-19 Infectionmentioning
confidence: 99%
“…Randomized controlled trials also confirmed the efficacy and safety of XFBD therapy for COVID-19. This treatment improved the conversion time of negative nucleic acid tests to positive, the duration of hospital stay, disease symptoms, and lung CT imaging in COVID-19 patients [83] . Another clinical trial compared a single conventional drug and its combination with XFBD and discovered that the combined treatment significantly reduced symptoms like fever, fatigue, and cough, and loss of appetite in 42 COVID-19 patients.…”
Section: Leading Six Tcm Influential Roles In Treating Covid-19mentioning
confidence: 96%
“…Xuanfei Baidu (XFBD) is a prescription recommended by the State Administration of Traditional Chinese Medicine for the clinical treatment of COVID-19 ( Zhao et al, 2021 ). This prescription is a traditional Chinese medicine formula proposed by Academician Zhang Boli and Professor Liu Qingquan on the anti-epidemic front line.…”
Section: Introductionmentioning
confidence: 99%